Brazilian Society of Surgical Oncology considerations on gynecologic cancer management during COVID-19 pandemic - Baiocchi, Glauco; Coelho, Eid Gonçalves; Batista, Thales Paulo; Guitmann, Gustavo; Fernandes, Paulo Henrique de Sousa; Ribeiro, Reitan; Ribeiro, Heber Salvador de Castro; Oliveira, Alexandre Ferreira; Tsunoda, Audrey Tieko (Brazilian Journal of Oncology, 2020)
The present proposal aims to support and help clinicians how to manage gynecologic cancer patients during the COVID-19 pandemic. It is based on the opinions of surgical oncologists of the Brazilian Society of Surgical Oncology (BSSO) and not necessarily evidence-based instructions.
Keywords: COVID-19 pandemic; surgical oncology; gynecologic cancer